أنواع المصادر ودلالتها في سورة المزمل - Nadhif f; maslamah h (UIN Fatmawati Sukarno Bengkulu, 2022)
ABSTRACTMasdar is considered as one of the most extensive and most difficult morphology discussions by students. This is because there are many types of masdar accompanied by different meanings and the different of wazan masdar. This study aims to find out the various types of Masdar in al-Muzammil and their meanings. This research aims to know the types of masdar and their significance in surat al-Muzammil and to facilitate students in understanding it deeply and accurately. This research is qualitative descriptive research. The data are collected by identifying the verses that contain the masdar, then analyzed by descriptive analysis, wich by identifying the type of masdar and their significance. The results of the research are that the masdar in surat al-Muzammil is twenty two, and it is published in eleven verses. Five for the isimmasdar, one for the masdarmuawwal, and the rest for a general masdar. The indication of the meanings of the masdaristwo, they are the event only and the event with emphasis.Keywords: Masdar, Al-Muzammil, Significance